COEFFICIENT VALUE OF NUTRITIONAL FISH AND DIVERSITY PLANKTON LAKE RAWA PENING JAWA TENGAH - Sukiya Sukiya (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2003)
The objective of the research is to investigate the nutrition vaLuecoefficient of fish and plankton diversity of Rawapening Lake due to pollutant from inlet water. Research was conducted in west, middle and south sides of the lake. The independent variable was the physicochemical quality of the water body, and the dependent one was the nutrition value coefficient of fish and plankton diversity. Samples were the mixture of 10 litres surface and 10 litres of two-meter deep' waterfor every station sampled. Temperature, clarity, total suspended solid and pH measured in situ. Microwinkler method was applied to measure alcalinity, DO and free CO2 in water body. Identification of plankton diversity used the book of Fresh Water Biology by Edmonson published in 1966 and Planktonology by Sachlan published in 1978, the nutrition value coefficient of fish was calculated using Fulton formula. Results show that 43 plankton and 16 necton species are investigated. Based on the coefficient of nutrition value it is concluded that Rawapening lake is consideredfeasiblefor nilafish (Oreochromys nilotica) to culture.